PENGARUH KUALITAS AKTIVA PRODUKTIF TERHADAP PROFITABILITAS BANK UMUM SYARIAH - Widhiati, Iksanti Nur (Universitas Negeri Surabaya, 2021)
Islamic banks have a profit or profit orientation. The profit earned is not only for the benefit of the owner or founder, but is also very important in the development of a Islamic banks business. previous period. The condition of financial performance is used as a material for consideration in deciding managerial policies that will be in line with aspects of the banking world. Assessment on the quality of earning assets is intended to assess how the condition of assets obtained by the bank, also includes anticipation of the risk of payment failure through existing financing. Due to the high risk of earning assets, banks should set aside a portion of the profits to form risk reserves for earning assets. This research aimed to analyze the effect of the variable quality of eaming on the profitability of Islamic commercial banks for the 2014-2018 period. This research was an associative study using simple linear regression. The results showed that the quality of eaming asseats has a positive and significant on the profitability of Islamic commercial.